Elevated Circulating Fibrocytes Is a Marker of Left Atrial Fibrosis and Recurrence of Persistent Atrial Fibrillation. Issue 6 (13th March 2018) - Liu, Yang; Niu, Xiao‐Hui; Yin, Xiaomeng; Liu, Yue‐Jian; Han, Chao; Yang, Jie; Huang, Xin; Yu, Xiaohong; Gao, Lianjun; Yang, Yan‐Zong; Xia, Yun‐Long; Li, Hui‐Hua
Abstract : Background: In atrial fibrillation (AF), a more extensively fibrotic left atrium (LA) provides a substrate for arrhythmias and increases risk of relapse following ablation. Fibrocytes are bone marrow–derived circulating mesenchymal progenitors that have been identified in the atrium of patients with AF who have valvular diseases. The present study investigates the associations between circulating fibrocytes and LA fibrosis or the prevalence of recurrence after ablation in patients with persistent AF. Methods and Results: We measured the proportion, differentiation, and migration of circulating fibrocytes from patients with persistent AF (n=40), those with paroxysmal AF (n=30), and sinus rhythm controls (n=30). LA low‐voltage (fibrosis) area was identified by an electroanatomic mapping system, and patients were followed up for 1 year after ablation. The relationship between circulating fibrocyte percentage and LA low‐voltage area or recurrence was assessed by multivariate regression analysis. Circulating fibrocyte percentage positively associated with LA low‐voltage area in the persistent AF group, and circulating fibrocyte (≥4.05%) was a significant predictor of 1‐year recurrence after ablation. Cultured fibrocytes exhibited enhanced potential of differentiation in the persistent AF group (67.58±1.54%) versus the paroxysmal AF group (56.67±1.52%) and sinus rhythm controls (48.43±1.79%). Furthermore, expression of fibroblast activation markers and cell migratory ability were also elevated in differentiated fibrocytes from patients with persistent AF. Transforming growth factor β1 and stromal cell–derived factor 1 were elevated in the plasma of patients with persistent AF and were shown to promote fibrocyte differentiation and migration, respectively. Conclusions: In patients with persistent AF, increased circulating fibrocytes served as a marker of LA fibrosis and recurrence.